STUDI PRELIMINARI TENTANG PENGARUH D-GALAKTOSA DALAM MENGINDUKSI STRES OKSIDATIF PADA MENCIT JANTAN GALUR OUTBRED FK USU - Bintang, Siti Sarah Bintang Sarah; Siregar, Yahwardiah; Ichwan, Muhammad (Jurnal FARMASIMED (JFM), 2019)
Abstract Oxidative stress occurs due to imbalance of free radicals over antioxidant level in the body. This condition causes lipid peroxidation and DNA damage. D-Galaktosa is The mechanism of oxidative stress induced by d-galactose occurs in the subcellular, especially in the brain's mitochondria. Increasing the concentration of d-galaktosa is oxidized by galaktosa oxidase to form hydrogen peroxide (H202) which causes a decrease in superoxide dismutase (SOD). H202 reacts with reduced iron and forms hydroxide ions (OH-). Objective: The aim of this study was to determine the effect of d-galaktosa induction on oxidative stress levels (MDA) in male mice. Methods: Methods of samples of mice given d-galaktosa and blood collection from the heart were carried out at the Pharmacology Laboratory of the Faculty of Medicine, University of North Sumatra. Results: The results showed that administration of d-galaktosa, through intraperitonial injection every day for 6 weeks, had an effect on the levels of oxidative stress in male mice. Conclusion: The results of this study indicate that administration of d-galaktosa, through intraperitonial injection every day for 6 weeks, has an effect on levels of oxidative stress in male mice.